Control Mechanism of Particle Flow in the Weak Liquid Metal Flow Field on Non-Uniform Curvature Surface Based on Lippmann Model - Zhang, Li; Zheng, Bingjun; Xie, Yi; Ji, Renquan; Li, Yanbiao; Mao, Wenbing (Frontiers in Materials, 2022)
In order to realize the uniform distribution in the abrasive flow polishing of the titanium alloy workpiece with curved surface, a novel method based on the liquid metal-abrasive flow machining technology is proposed in this study. Based on the SST k-ω model, Preston model and fluid flow particle tracking model, the COMSOL software is employed to study the dynamic characteristics of liquid metal-abrasive flow under different AC electric field conditions, and the two-phase flow field is used to simulate the liquid state, the movement of liquid metal particles on the surface of the workpiece and the varitation of the Pv value in the near-wall region. It is found from numerical simulation results that the average Pv value in the strong flow field is 23718.8 W/m², and that in the weak flow field is 5427.3 W/m². By the assistance of the electric filed with the voltage of AC 36V, the average Pv value of the liquid metal particles in the weak flow field is found to be 10948.6 W/m² with an increase of 101.7%. Therefore, to properly control the electric field strength, the movement of liquid metal in the flow field can be found to be controlled, and hence improving the uniformity of the turbulent kinetic energy on the workpiece surface and improving the processing quality.